2005
DOI: 10.1080/10810730500257754
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Tailored Print Materials in Promoting Colorectal Cancer Screening: Results From a Randomized Trial Involving Callers to the National Cancer Institute's Cancer Information Service

Abstract: In this large randomized trial among callers to the Cancer Information Service (CIS), tailored print materials were tested for efficacy in promoting colorectal cancer (CRC) screening (fecal occult blood test [FOBT], flexible sigmoidoscopy, or colonoscopy). All participants completed baseline interviews at the end of their usual service calls to the CIS, as well as short-term (6-month) and longer-term (14-month) telephone follow-up interviews. The study sample (n = 4,014) was restricted to English-speaking CIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 43 publications
3
62
0
Order By: Relevance
“…Of previous randomized controlled trials comparing a sociopsychologically tailored colorectal cancer screening intervention with an active control, 15,19,20,22,[25][26][27][28][29][30]33 only some reported improvements in screening, 19,25,28,29,34 in most instances based on patient report, 19,25,28,29 suggesting possible misclassification bias. These observations, plus our current findings, raise doubts about the superiority of sociopsychological tailoring to nontailored approaches in promoting colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of previous randomized controlled trials comparing a sociopsychologically tailored colorectal cancer screening intervention with an active control, 15,19,20,22,[25][26][27][28][29][30]33 only some reported improvements in screening, 19,25,28,29,34 in most instances based on patient report, 19,25,28,29 suggesting possible misclassification bias. These observations, plus our current findings, raise doubts about the superiority of sociopsychological tailoring to nontailored approaches in promoting colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22] Whether enhancement of sociopsychological factors influences health behaviors is uncertain. 12,13,19,[22][23][24][25][26][27][28][29][30][31][32] Among trials comparing patients receiving sociopsychologically tailored colorectal cancer screening interventions with active control, 15,19,20,22,[25][26][27][28][29][30]33 only some found superior effects of tailoring 19,25,28,29,34 ; in all but 1 trial 34 screening was self-reported, 19,25,28,29 suggesting possible response bias. There is a need to examine further whether objectively measured colorectal cancer screening improves in response to sociopsychologi...…”
Section: Introductionmentioning
confidence: 99%
“…The research protocol was approved by the institutional review boards at both the University of California, San Francisco and the Northern California Cancer Center. Similar research using telephone lines to implement various types of health interventions has been performed in diverse settings for non-minority populations (Darrow et al 1998;Davis et al 2004;Heimendinger et al 2005;Marcus et al 2005;Miller et al 2005;Strecher et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Marcus and colleagues conducted one of the few randomized trials to examine the efficacy of tailored print materials to promote CRC screening among callers to the Cancer Information Service [16]. These investigators used a 4-group design and enrolled more than 4000 callers to the Cancer Information Service to test the effects of tailoring, multiple mailouts, and retailoring of print materials.…”
Section: Introductionmentioning
confidence: 99%